Cover Image. Issue 9 (12th August 2019) - Nucci, Marcio; Engelhardt, Marc; Hamed, Kamal
Abstract : The cover image is based on the REVIEW ARTICLE Mucormycosis in South America: A review of 143 reported cases by Marcio Nucci** et al., https://doi.org//10.1111/myc.12958 .*** Cover image © Kamal Hamed and Jim Park Images